Studies on the Physiological and Biochemical Composition of Different Mango Cultivars at Various Maturity Levels (Bangladesh Journal of Scientific and Industrial Research, 2007)
A comparative study on physiological and biochemical composition of ten varieties of mangoes was carried out at three maturity stages viz. immature, mature and ripe to find out the standard one. During the investigation, whole weight of the mangoes, pulp content, weight of peel and stone, total soluble solid (TSS), pH, acidity, sugar content and vitamin C were determined at three maturity stages. It was observed that all the varieties at ripe stages had higher sugar content as compared to immature and mature stages. Attractive flavour and pleasant taste were also developed in ripe stages and differed from one another due to varietal specific. This characteristics odour which appeared during ripening is due to ester and components of carbonyl types. Bangladesh J. Sci. Ind. Res. 41(1-2), 101-108, 2006